MOCK OBSERVATIONS OF SIMULATED STAR CLUSTER ON SOLAR ORBIT - Kalambay, M.T.; Naurzbayeva, A.Zh.; Otebay, A.B.; Abdinassilimm, A.T.; Kuvatova, D.; Assilkhan, A.D.; Panamarev, T.; Shukirgaliyev, B.T.; Berczik, P.P. (Recent Contributions to Physics, 2022)
With the advent of the Gaia DR2 catalog, which contains astrometric and photometric parameters for a large number of stars, measured with a high degree of accuracy, data about the cosmos and the Universe, including Star clusters in our Galaxy, are growing. However, when observed, the cluster stars are lost against the background of stars in the dense Galactic field. In addition, observational data alone is not sufficient to study real clusters from birth to destruction. In this regard, a number of numerical simulations of star clusters have been running to explain the processes and to determine the membership of cluster stars. And for this, we need to conduct a mock observation of model clusters. In this paper, we performed analyses on the output data from numerical simulations and developed a method for conducting mock observations of model clusters.We took one model of a star cluster with an age of 350 Myr, with a mass of 6000 , and with a star formation efficiency SFE=0.25, and put it in different galactic longitudes and at different distances from the Sun. In conclusion, using this method, we can put a cluster at any point on the celestial sphere, and this in turn allows you to compare with the real observed clusters and evaluate the possibility of detecting physical parameters in them.